The influence of ground control footwear on knee joint moments during running - Stefanyshyn, D. J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Subjects who developed patellofemoral pain syndrome during running had higher internal knee abduction and external rotation moments than asymptomatic subjects (Stefanyshyn et al., in press). Footwear can significantly influence joint moments at the knee and ankle (Mündermann et al., 2003). Therefore, it was speculated that footwear could be developed specifically to reduce knee joint moments, primarily in the transverse and frontal planes. New prototypes were developed to allow the foot to displace both in a medial-lateral and anterior-posterior direction relative to the outsole. The purpose of this study was to determine if the prototype footwear allowing relative movement between the foot and outsole would reduce three-dimensional knee joint moments during running.